Why Did Your Project Fail? - CERPA, NARCISO; VERNER, JUNE M. (Communications of the ACM, 2009)
The article discusses the reasons for the failure of software development projects. Several suggested reasons are mentioned, including scheduling problems, cost overruns, and constantly-changing user requirements. The expense and difficulty of developing software systems is discussed, noting that minimal understanding is gained from the results of past software development projects; project managers (PMs) must balance pressures from stakeholders such as their company's upper management, marketing department, and accounting department; and the influence of such pressures upon the cost and quality of the final software product.